2021
DOI: 10.1002/humu.24196
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of multigene panel NGS diagnosis in the national primary ciliary dyskinesia cohort of Cyprus: An island with a high disease prevalence

Abstract: We aimed to determine a genetic diagnosis in the national primary ciliary dyskinesia (PCD) cohort of Cyprus, an island with a high disease prevalence. We used targeted next-generation sequencing (NGS) of 39 PCD genes in 48 patients of Greek-Cypriot and other ancestries. We achieved a molecular diagnosis in 74% of the unrelated families tested. We identified 24 different mutations in 11 genes, 12 of which are novel. Homozygosity was more common in Greek-Cypriot than non-Greek-Cypriot patients (88% vs. 46.2%, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…However, it was already suspected that the previously understood leading causes of PCD may be heavily biased towards European/north American populations, as these are the so-far best studied. The emerging view, that specific ethnicities carry characteristic PCD gene variants, concurs with previous reports of different human populations carrying their own specific mutational landscape and predominant PCD disease variants [4][5][6][7] . Overall, this study highlights a need for new understanding about the most at-risk communities.…”
supporting
confidence: 88%
“…However, it was already suspected that the previously understood leading causes of PCD may be heavily biased towards European/north American populations, as these are the so-far best studied. The emerging view, that specific ethnicities carry characteristic PCD gene variants, concurs with previous reports of different human populations carrying their own specific mutational landscape and predominant PCD disease variants [4][5][6][7] . Overall, this study highlights a need for new understanding about the most at-risk communities.…”
supporting
confidence: 88%
“…In this study we have identified a mutation in CFAP300 causative for PCD in Finland and analysed the effect of the mutation on motile cilia formation and function. The main defect in axonemal cross-sections was the lack of dynein arms as described in previous studies (Fassad et al, 2018;Höben et al, 2018;Zietkiewicz et al, 2019;Aprea et al, 2021;Bolkier et al, 2021;Yiallouros et al, 2021). Furthermore, we detected misorientation of the basal feet of the airway cilia, which we believe is most likely to be a secondary defect due to the lack of cilia motility and is also seen in PCD cases due to mutations in other genes.…”
Section: Discussionsupporting
confidence: 81%
“…Although we were unable to confirm the axonemal defects in this patient, the residual movement could be due to different levels of dynein arm formation as has been shown in previous studies (Fassad et al, 2018;Aprea et al, 2021;Yiallouros et al, 2021). Variable cilia beat frequency has also been reported for variant c.98_106del (0-9.1 Hz, Yiallouros et al, 2021). All the CFAP300 mutations reported to date are listed in Table 2.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…There seems to be a genotype/phenotype correlation in PCD, with subjects carrying mutations, e.g. in the genes CCDC40 [ 6 ] or CCNO [ 7 ], displaying worse lung function outcomes and individuals with mutations in, for example, DNAH9 , RSPH1 and RSPH9 showing milder respiratory phenotypes, as reported in small cohorts [ 1 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%